2000
DOI: 10.1128/mcb.20.1.329-339.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Ustilago maydisGene Specifically Induced during the Biotrophic Phase: Evidence for Negative as Well as Positive Regulation

Abstract: The phytopathogenic basidiomycete Ustilago maydis requires its host plant, maize, for completion of its sexual cycle. To investigate the molecular events during infection, we used differential display to identify plant-induced U. maydis genes. We describe the U. maydis gene mig1 (for "maize-induced gene"), which is not expressed during yeast-like growth of the fungus, is weakly expressed during filamentous growth in axenic culture, but is extensively upregulated during plant infection. mig1 encodes a small, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 44 publications
0
87
0
1
Order By: Relevance
“…The function of these features is still unclear. For other plant induced genes, like MIG1 and LtmM, serial deletions in the promoter region provided information on the different effects of subregions on expression levels (Basse et al, 2000;May et al, 2008). LtmM expression was also shown to vary depending on the type of infected tissue (May et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of these features is still unclear. For other plant induced genes, like MIG1 and LtmM, serial deletions in the promoter region provided information on the different effects of subregions on expression levels (Basse et al, 2000;May et al, 2008). LtmM expression was also shown to vary depending on the type of infected tissue (May et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For Avr9 and Mpg1 it was shown that expression (partly) depends on a general nitrogen response factors (NRF1 and NPR1, respectively) (Lau and Hamer, 1996;Perez-Garcia et al, 2001;Soanes et al, 2002). However, expression of other in planta induced genes does not respond to changes in nitrogen availability, for example AVR4, ECP1 and ECP2 (C. fulvum), AvrLm1 (Leptosphaeria maculans), MIG1 and the MIG2 gene cluster (Ustilago maydis) (Basse et al, 2002(Basse et al, , 2000Gout et al, 2006;Van den Ackerveken et al, 1994;Wubben et al, 1994). Even for the genes that are expressed in an environment with limited nitrogen, it is not known which circumstances induce expression in planta, since there are indications that within the host plant, nitrogen is not limiting Oliver, 2001, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It encodes secreted small proteins that contribute to the hydrophobicity of the fungal cell wall. Another gene, mig1, which is highly expressed during growth in the plant, was identified by differential display (Basse et al, 2000). From its derived amino acid sequence it was concluded that mig1 encodes a small, highly charged protein of unknown function which contains a functional Nterminal secretion sequence.…”
Section: Isolation Of Pathogenicity Genes By Their Specific Expressiomentioning
confidence: 99%
“…The promoter of this gene has been analysed for regulatory elements that are responsible for the expression pattern. It has been shown that this gene is subject to both negative and positive control (Basse et al, 2000). The detailed analysis of additional genes that exhibit a similar expression pattern will help to elucidate common regulatory elements involved in the activation of hostinduced genes.…”
Section: Isolation Of Pathogenicity Genes By Their Specific Expressiomentioning
confidence: 99%
See 1 more Smart Citation